2017
DOI: 10.1097/ajp.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Happy Despite Pain

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 64 publications
2
67
0
Order By: Relevance
“…A similar technique is the Best Possible Self, which aims to increase optimism [ 68 71 ]. Finally, a recent study demonstrated the clinical usefulness of an Internet-based positive psychology self-help intervention for the management of chronic pain [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar technique is the Best Possible Self, which aims to increase optimism [ 68 71 ]. Finally, a recent study demonstrated the clinical usefulness of an Internet-based positive psychology self-help intervention for the management of chronic pain [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has confirmed that PPI effectively improves subjective and psychological well-being and reduces depressive symptoms [ 62 ]. Furthermore, there were no significant differences between internet PPI and internet cognitive behavioural therapy (iCBT) at the 6-month follow-up for depression or for happiness [ 63 ]. Both interventions are effective in reducing depression and increasing happiness.…”
Section: Discussionmentioning
confidence: 99%
“…While previous literature indicates a negative association between VI and psychological well-being [1-6, 23], many studies in the field of positive psychology claim that using strengths is energizing [24] and focusing on the positive assets in persons with disabilities could generate positive emotions for building resilience [25]. In addition, Peters et aldemonstrate that positive psychology intervention could improve pain intensity and pain control in persons with chronic pain [26].…”
Section: Discussionmentioning
confidence: 99%